Special issue: Building bridges between researchers and practitioners - Javier Santos; Elisabeth Viles (Journal of Industrial Engineering and Management (JIEM), 2016)
This special issue of the Journal of Industrial Engineering and Management is focused on the most recent and relevant research, theories and practices in Industrial Engineering and Operations Management presented at the International Joint Conference (IJC2016). This International Joint Conference is a result of an agreement between ADINGOR (Asociación para el desarrollo de la Ingeniería de Organización), ABEPRO (Associaçâo Brasileira de Engenharia de Produçâo), IISE (Institute of Industrial & Systems Engineers) and AIM (European Academy for Industrial Management). The conference was organised by the Industrial Management Department at Tecnun (School of Engineering - University of Navarra).
Keywords: 650